Heat Partition between the Friction Components in Multi-disc Clutch during Sliding - Xiong Cenbo; Ma Biao; Li Heyan; Zhang Fenglian; Zhu Li’an (Jixie chuandong)
During the sliding process of multi- disc clutch,the heat partition coefficient between friction components is affected by the disc thickness and material property. For the discs with finite thickness,a coupled heat conduction model is established,based on which the disc temperature fields and the heat partition coefficient are obtained at the same time. The results show that,the heat partition coefficient is a constant at the very beginning and varies to another steady- state constant after a short time rise. Comparing this heat partition coefficient with the constant value obtained by the semi- infinite model,it’s found that the latter can only determine the initial heat partition coefficient. Experimental results show that,the temperature field calculated with variable heat partition coefficient is very close to the measured temperatures. However,the temperature field predicted with the constant heat partition coefficient overestimates the separator disc temperature and underestimates the temperature of the friction disc.